2016
DOI: 10.1371/journal.pone.0148565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Copy Number Variations in Xiang and Kele Pigs

Abstract: Xiang and Kele pigs are two well-known local Chinese pig breeds that possess rich genetic resources and have enormous economic and scientific value. We performed a comprehensive genomic analysis of the copy number variations (CNVs) in these breeds. CNVs are one of the most important forms of genomic variation and have profound effects on phenotypic variation. In this study, PorcineSNP60 genotyping data from 98 Xiang pigs and 22 Kele pigs were used to identify CNVs. In total, 172 candidate CNV regions (CNVRs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…We also compared our results with previous studies on CNVRs, which showed a low overlap rate [17,35,44,46,54,[57][58][59][60]. In brief, a total of 404 CNVRs entirely or partially overlapped with the previously reported CNVRs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We also compared our results with previous studies on CNVRs, which showed a low overlap rate [17,35,44,46,54,[57][58][59][60]. In brief, a total of 404 CNVRs entirely or partially overlapped with the previously reported CNVRs.…”
Section: Discussionsupporting
confidence: 52%
“…In brief, a total of 404 CNVRs entirely or partially overlapped with the previously reported CNVRs. A considerable overlap rate was observed in the results of Zheng et al [17], while that of Xie et al [60] was the lowest. These discrepant observations may be due to the difference in the breed and population size between our study and others.…”
Section: Discussionmentioning
confidence: 78%
“…Although several methodologies have been applied to detect CNVs in the pig genome, SNP arrays have better properties, such as lower cost compared to next generation sequencing (NGS) methodology and can be used for both GWAS and CNV detections. Employing SNP for CNV detection, previous studies have identified thousands of porcine CNVs [12, 1628]. Because most of these studies comprised relatively small numbers of animals, the impacts of CNVs on phenotypes are still relatively poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] also identified 368 unique CNV regions from 265 Korean Hanwoo cattle based on 50K SNP array covering 15.8Mb of the genome using PennCNV algorithm without considering the pedigree information and genomic waves. Recent studies on CNV detection using different approaches are given in the Table-1 [ 11 - 14 , 23 , 30 , 34 - 37 , 42 - 46 ] for cattle and Table-2 [ 14 , 16 , 47 - 52 ] for other species.…”
Section: Cnv Identification Studies In Domestic Speciesmentioning
confidence: 99%